Assessment of Surface Modification by Laser Studies of Polymer Material before and after MB Doping - Zamil Abdulzahra , Narjis (New Trends in Physical Science Research Vol. 1, 2022)
In this research the PVA surface temperature before and after laser radiation was calculated depending on optical properties (absorption , transmission , reflection spectra, optical absorption coefficient) and thermal properties calculations (weight after doping, density and thermal diffusivity),the surface temperature decreased after adding low doping concertation(134 to 77)C at laser fluence 20J/cm2 because MB works as a trapping center so it dispersed laser energy, by increasing doping concentration to (0.04 g) the surface temperature increased to 181 C due to increased absorption coefficient (12 to 53 cm-1)and decreased thermal diffusivity(43 to5)×10-7 m2/s ,by increasing laser intensity the surface temperature increased (216 to290C)at laser flunce32 J/cm2 and (337 to 453C) at 50 J/cm2 .The UV–vis study of these materials indicates that MB forms a complex with the polymer by a hydrogen bonding interaction between the –OH group of the polymer and the nitrogen of MB and improves the thermal stability of the polymer. The aims of this research to study the surface temperature of PVA before and after MB doping dependent on measured optical properties and thermal constants.